2011
DOI: 10.1128/aac.00032-11
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hepatitis C Virus Replicon RNA Synthesis by PSI-352938, a Cyclic Phosphate Prodrug of β-d-2′-Deoxy-2′-α-Fluoro-2′-β-C-Methylguanosine

Abstract: PSI-352938 is a novel cyclic phosphate prodrug of ␤-D-2-deoxy-2-␣-fluoro-2-␤-C-methylguanosine 5-monophosphate that has potent activity against hepatitis C virus (HCV) in vitro. The studies described here characterize the in vitro anti-HCV activity of PSI-352938, alone and in combination with other inhibitors of HCV, and the cross-resistance profile of PSI-352938. The effective concentration required to achieve 50% inhibition for PSI-352938, determined using genotype 1a-, 1b-, and 2a-derived replicons stably e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…1. Previously we reported that replicons containing the NS5B amino acid change S96T or S282T, which confers resistance to certain nucleoside/-tide analogs, or amino acid changes (C316Y, M414T, M423T, or P495L) that confer resistance to various classes of nonnucleoside inhibitors remained fully susceptible to both PSI-352938 and PSI-353661 (4,11). In order to identify the mutation(s) that confers resistance to these compounds, selection studies were performed using replicon cells and increasing concentrations of PSI-352938 or PSI-353661.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1. Previously we reported that replicons containing the NS5B amino acid change S96T or S282T, which confers resistance to certain nucleoside/-tide analogs, or amino acid changes (C316Y, M414T, M423T, or P495L) that confer resistance to various classes of nonnucleoside inhibitors remained fully susceptible to both PSI-352938 and PSI-353661 (4,11). In order to identify the mutation(s) that confers resistance to these compounds, selection studies were performed using replicon cells and increasing concentrations of PSI-352938 or PSI-353661.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolism of PSI-352938 and PSI-353661 generates the same 5Ј-triphosphate metabolite, PSI-352666 (2Ј-F-2Ј-C-methylguanosine-triphosphate), which is similarly active against NS5B polymerases from GT 1 to 4 (11). Our previous cross-resistance studies also showed that PSI-352938 and PSI-353661 remained fully active against both the S96T and S282T replicons (4,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been reported that PSI-6130, INX-189, and IDX-184 were less active against GT 1b S282T replicons (26,40,43). In addition, we included in these studies PSI-352938, a prodrug of 2=-F-2=-C-methylguanosine monophosphate that remains active against GT 1b replicons with the S282T change (16). Results are summarized in Table 6.…”
Section: Figmentioning
confidence: 99%
“…Among the compounds synthesized and tested, PSI-352938, a novel cyclic phosphate prodrug of ␤-D-2=-fluoro-2=-C-methylguanosine 5=-monophosphate with pangenotypic anti-HCV activity, showed the best profile in terms of anti-HCV activity, cytotoxicity, stability, and intracellular triphosphate production (26). Furthermore, PSI-352938 lacked cross-resistance with other modified nucleoside/nucleotide analogs targeting HCV NS5B (18), suggesting that a comple-mentary effect could be achieved when combined with other classes of nucleoside/nucleotide inhibitors. Since we previously demonstrated that the metabolism of PSI-7851, a phosphoramidate prodrug of ␤-D-2=-deoxy-2=-␣-fluoro-2=-␤-C-methyluridine-5=-monophosphate, and the metabolism of its single isomer, PSI-7977, were different in Huh 7-derived clone A replicon cells and primary human hepatocytes due to differences in the expression of certain enzymes involved in the metabolism of these compounds, we compared the metabolisms of PSI-352938 in these two cell types (24).…”
mentioning
confidence: 99%